MEMAKNAI NILAI MALAQBIQ DALAM AKUNTABILITAS PENGELOLAAN KEUANGAN PADA KOMUNITAS SJS - Sakinah Saharuna; Alimuddin Alimuddin; Sri Sundari (Jurnal Ilmiah Global Education, 2023)
This study aims to reveal and find out how financial management accountability practices are carried out from the perspective of cultural values contained in the Friday alms community of South Sulawesi. This research uses a qualitative approach with phenomenological methods that take the Friday Sulbar alms community as a research site. Data collection was done in a natural setting through participatory observation, documentation and in-depth interviews. The data analysis technique uses a modified and simplified Smith analysis model in the form of transcripts. The results showed that the SJS Community interprets the cultural value of malaqbiq in the practice of accountability by members of the Sulbar Friday alms community, from every practice action produced; there are values that surround it, namely the value of Malaqbiq. Financial management in the South Sulawesi Friday Alms community goes through two processes, namely the planning and implementation process. Planning is carried out in small discussions through Whatsapp groups, which involve all competent and involved elements in the organization. The process of implementing alms at the South Sulawesi Friday Alms Community is carried out in accordance with several existing programs.